Attitude Markers and Engagement Markers in Creative Arts Journal Papers - Afifah, Nawawi; Ting, Su Hie (2022)
In academic contexts, writers use interactional metadiscourse markers to show their attitude toward readers in the process of constructing the text (Hyland, 2005). For example, writers may comment on the information in the text by subtly showing their personal attitudes towards the information. By engaging with readers, writers increase the persuasiveness of the text (Hyland, 2005). Interactional metadiscourse markers include boosters, hedges, attitude markers, engagement markers and selfmentions. This paper focuses on attitude markers and engagement markers. Attitude markers are used by writers to convey their agreement, surprise or disbelief towards a proposition, thereby allowing readers to recognise their view on the subject matter. To make their views clear and explicit, writers can use a selection of verbs (e.g., “prefer”), adverbs (e.g., “amazingly”) and adjectives (e.g., “interesting”). Aside from that, engagement markers act as a way for the writers to build a relationship with their readers. Engagement markers allow writers to acknowledge their readers and involve them in the discussion of the subject matter at hand. Examples of engagement markers are pronouns (e.g., “we”), interjections (e.g., “by the way”), directives (e.g., “consider this”), obligation modals (e.g., “should”), shared knowledge (e.g., “it is well known”) and questions. The use of interactional markers has been found to depend on factors such as discipline (e.g., biology and applied linguistics) and rhetorical section (e.g., introduction, method, results, discussion, conclusion), as shown by past studies (Hu & Cao, 2015; Khedri & Kritsis, 2018). However, there is a lack of findings on how interactional metadiscourse markers are used in some disciplines such as creative arts. It is important to study how interactional metadiscourse markers are used in creative arts journals because the subject matter is creative and there is more subjectivity involved. Creative arts research generally produce a less tangible form of knowledge and do not always provide data that can be analysed for objectivity, reliability and validity (Foster, 2012). Analysis of how attitude and engagement are manifested in creative arts journal papers would add to knowledge on disciplinary differences in metadiscourse use. The present study examined the distribution of attitude markers and engagement markers in creative arts journal papers. The study focused on: (1) comparison of frequencies of attitude markers and engagement markers in Q1 and Q3-Q4 journal papers, and (2) the distribution of attitude markers and engagement markers by rhetorical section of journal papers. For the corpus, 40 papers were selected, which are 20 Quartile 1 (Q1) and 20 Quartiles 3 and 4 (Q3-4) from eight journals. The Q1 journals were Cultural Trends, Fashion Theory, Empirical Studies of the Arts and Visual Communication while the Q3-Q4 journals were Dress, South African Theatre Journal, Journal of Historical Research in Music Education and Street Art and Urban Creativity. All of the selected journal papers were: (1) published in 2011-2021, and (2) organised into rhetorical sections like abstract, introduction, method, results, discussion, and conclusion. The coding process was conducted using a framework adapted from Hyland’s (2005) interpersonal metadiscourse model.The results showed that there were 1,525 attitude markers and engagement markers in the journal papers, with higher frequency of attitude markers (69.70%) than engagement markers (30.30%). The frequent use of attitude markers indicate that the creative arts researchers were inclined to reveal their personal views on the subject matter, whether it is their agreement, surprise or disbelief towards a proposition. Examples of attitude markers used in the creative arts journal papers were adjectives (e.g., “important”, “crucial”) to express the importance of a proposition. Engagement markers were less frequently used than attitudes markers in all the rhetorical sections in the creative arts journal papers. To engage their readers, the creative arts researchers used directives to get them into the discussion (e.g., “remember”, “keep in mind”). In addition, questions were used to elicit a response from readers (e.g., “What exactly does one mean when they say media traits are transferred or relocated from one medium to another?”). Aside from that, the creative arts researchers also used pronouns (e.g., “you”) and determiners (e.g., “your”) to address the readers directly. A comparison of the two types of markers in Q1 and Q3-4 journal papers showed that the creative arts researchers used these markers with similar frequencies regardless of whether they were writing for high or moderate ranked journals. In the Q1 journal papers, 65.63% of 742 markers were attitude markers and 34.37% were engagement markers. In Q3-Q4 journal papers, 73.56% of 783 markers were attitude markers and 26.44% were engagement markers. Additionally, this frequency pattern was also observed throughout all the rhetorical sections in the Q1 and Q3-Q4 papers. The attitude markers and engagement markers were used the most in results, discussion, and conclusion sections, followed by the introduction section, method section and the abstract section. Attitude marker is the most important in the results, discussion, and conclusion sections. These sections require writers to be evaluative when interpreting the results. The conclusion is the space for researchers to express their hope or recommendations for future research. Therefore, adverbial items (e.g., “hopefully”, “profoundly”) were commonly used in the results, discussion, and conclusion sections. This study shows that in creative arts journal papers, more attitude markers were used than engagement markers. The creative arts researchers seemed to be more comfortable in sharing their attitudes towards a proposition rather than engaging directly with their readers. This is a characteristic of academic writing where the focus of interest is on the subject matter rather than the audience. Selected References: Foster, V. (2012). The pleasure principle: Employing arts-based methods in social work research. European Journal of Social Work, 15(4), 532-545. Hu, G., & Cao, F. (2015). Disciplinary and paradigmatic influences on interactional metadiscourse research articles.